2006
DOI: 10.1021/ol061572c
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR-Based Empirical Rules to Determine the Configuration of Fatty Acid Butanolides. Novel γ-Dilactones from Pterogorgia spp

Abstract: Diastereomeric gamma-dilactones isolated from Pterogorgia spp allowed the establishment of (13)C NMR-based empirical rules to determine the relative stereochemistry of 3-alkyl-4-hydroxy-5-methyl-2(5H)-dihydrofuranones, gamma-lactone moieties ubiquitous in many bioactive synthetic and natural products. An NMR-based method using Pirkle's reagent at low temperature allowed the absolute configuration of the naturally occurring dibutenolides to be unambiguously determined. A biogenetic pathway that involves oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The relative configuration of the ring substituents were determined by comparison with NMR resonances of known compounds. NMR data of (2R,3R,4S)‐ and (2S,3R,4S)−2‐methyl‐3,4‐dihydroxypentanoic acid 1,4‐lactone, 5 S ,3′ R ,4′ S ,5′ S ‐ and 5 S ,3′ S ,4′ S ,5′ S ‐hydroxyancepsenolide as well as (2S*,3R*,4S*)‐2‐n‐hexadecyl‐3,4‐dihydroxypentanoic acid 1,4‐lactone (Lorenzo et al ., ) revealed that a trans ‐configuration of the 3‐OH to the 4‐methyl group causes a shielding of about δ H 0.3–0.7 ppm and a deshielding of about δ C 5 ppm compared with a cis ‐arrangement. 1 H NMR and optical rotation data of both the (2R,3R,4S)‐ trans , trans ‐ and (2S,3R,4S)‐ cis , trans ‐coprinuslactone reported by Bernardi et al .…”
Section: Resultsmentioning
confidence: 99%
“…The relative configuration of the ring substituents were determined by comparison with NMR resonances of known compounds. NMR data of (2R,3R,4S)‐ and (2S,3R,4S)−2‐methyl‐3,4‐dihydroxypentanoic acid 1,4‐lactone, 5 S ,3′ R ,4′ S ,5′ S ‐ and 5 S ,3′ S ,4′ S ,5′ S ‐hydroxyancepsenolide as well as (2S*,3R*,4S*)‐2‐n‐hexadecyl‐3,4‐dihydroxypentanoic acid 1,4‐lactone (Lorenzo et al ., ) revealed that a trans ‐configuration of the 3‐OH to the 4‐methyl group causes a shielding of about δ H 0.3–0.7 ppm and a deshielding of about δ C 5 ppm compared with a cis ‐arrangement. 1 H NMR and optical rotation data of both the (2R,3R,4S)‐ trans , trans ‐ and (2S,3R,4S)‐ cis , trans ‐coprinuslactone reported by Bernardi et al .…”
Section: Resultsmentioning
confidence: 99%
“…An NMR spectroscopic based method with the use of Pirkle's reagent at low temperature has proved to be useful to establish the absolute configuration of structurally diverse butenolide-containing compounds; for example, diterpenes, [11] fatty acid di-γ-lactones, [12] and annonaceous butenolides. [13] Now for the first time we apply this method with success to determine the absolute configuration at the ring closure carbon atom of a γ-and δ-lactone embedded in the chamigrene network of compounds 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of the relative stereochemistry of compound 1 was achieved using the NOESY spectrum in conjunction with the reported 13 C NMR values [18] from which the trans-trans-cis stereochemistry relationship of the lactones moiety was determined. Inspection of 13 C NMR spectrum suggest the trans configuration between C-5 methyl (δ C 18.2) and the hydroxyl group at C-4, when the methyl group is cis to hydroxyl group its 13 C NMR chemical shift is around δ C 13 and it is around δC 18 when it is trans to it [19].…”
Section: Identification Of Compound Imentioning
confidence: 99%
“…Also CH 2 (δ C 28.7) at C-3 is trans to hydroxyl group at C-4, if the CH 2 is cis to hydroxyl group its signal appears at around δ C 23 and it appear at around δ C 27 if its trans to it [16]. The actual relative configuration of the γ-lactone moiety was assigned to be 3R, 4R, 5S by comparing the δC values with the literature [18][19][20][21].…”
Section: Identification Of Compound Imentioning
confidence: 99%
See 1 more Smart Citation